Equilibrium stability of dynamic duopoly Cournot game under heterogeneous strategies, asymmetric information, and one-way R&D spillovers - Long Jianjun; Wang Fenglian (Nonlinear Engineering, 2023)
Bounded rationality, asymmetric information, and R&D spillovers are widely existed in monopoly markets, and they have been researched separately by a large number of literatures; however, there are few works that discussed both R&D spillovers and asymmetric information in oligopolistic games with bounded rational firms. Considering that R&D spillovers only flow from the R&D leader to the R&D follower, a duopoly Cournot game with heterogeneous expectations and asymmetric information is presented. In our model, a firm with private information of his marginal cost is designed, and the coefficient of R&D spillovers is introduced. Interesting findings show the following: (i) In a static duopoly Cournot game with perfect rationality, the equilibrium output of firm 1 with private information is negatively related to R&D spillovers and the probability of high marginal cost, while firm 2’s equilibrium output is positively correlated with them. (ii) In a dynamic duopoly Cournot game with asymmetric information and heterogeneous expectations, if firms adopt adaptive expectation and naïve expectation respectively, the Nash equilibrium is always globally asymptotically stable; if they use adaptive expectation and gradient dynamical expectation respectively, the Nash equilibrium tends to be locally asymptotically stable under certain conditions. Furthermore, the bigger the probability of high marginal cost or R&D spillovers are, the more volatile the monopoly market is, while higher technology innovation efficiency (TIE) of firm 1 is conducive to the stability of the product market. Our study would have theoretical and practical significance to the technological innovation activities of homogeneous products in oligopoly markets.